2013
DOI: 10.1080/00207144.2013.729439
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Validation of Two Differing Measures of Hypnotic Depth

Abstract: Several sets of regression analyses were completed, attempting to predict 2 measures of hypnotic depth: the self-reported hypnotic depth score and hypnoidal state score from variables of the Phenomenology of Consciousness Inventory: Hypnotic Assessment Procedure (PCI-HAP). When attempting to predict self-reported hypnotic depth, an R of .78 with Study 1 participants shrank to an r of .72 with Study 2 participants, suggesting mild shrinkage for this more attributional measure of hypnotic depth. Attempting to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…the srHD score. Several other works have been published concerning this score Pekala & Maurer, 2013). Additionally, Wagstaff (2010) wrote that the srHD score "is very similar to that found in the Long Stanford Scale of Hypnotic Depth (LSS)," (p. 49), suggesting commonalities between the srHD and LSS scores.…”
Section: Self-reported Hypnotic Depth (Srhd) Versus Hypnoidal Statementioning
confidence: 88%
See 2 more Smart Citations
“…the srHD score. Several other works have been published concerning this score Pekala & Maurer, 2013). Additionally, Wagstaff (2010) wrote that the srHD score "is very similar to that found in the Long Stanford Scale of Hypnotic Depth (LSS)," (p. 49), suggesting commonalities between the srHD and LSS scores.…”
Section: Self-reported Hypnotic Depth (Srhd) Versus Hypnoidal Statementioning
confidence: 88%
“…Hypnosis (Pekala & Maurer, 2013) did a cross-validation analysis of the hypnoidal and srHD scores; the results suggested that although there is some variance in common, the srHD score appears to be tapping a different construct from the hypnoidal state score. A correlation of .48 (p < .001) was found between the two constructs.…”
Section: An Article Published In the International Journal Of Clinicamentioning
confidence: 93%
See 1 more Smart Citation
“…If we are to accept the new definition, we are forced to disagree with Woody and Sadler's (2005) statement that hypnosis is not a dichotomous phenomenon. If the key parameters proposed by the new definition are present, we can state that an individual is in hypnosis; then and only then does it make sense to ask about hypnotic depth (see, for example, Pekala & Maurer, 2013) or hypnotizability (as defined by the HDC), both of which are considered constructs that vary in quantity. For example, if (1) a patient presents five or more of the symptoms listed in the DSM-V, (2) the symptoms have been present in the last 2 weeks, and (3) there has been a change in the individual's previous functioning, etc., then we can give the diagnosis of depression.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A hypnotic induction with suggestions for an analgesic reaction (Adachi, Fujino, Nakae, Mashimo, & Sasaki, 2014;Guttman & Ball, 2013) and pain threshold-tolerance tests were administered prior to 6 hours of REST, immediately after REST, and 10-14 days later. Results showed hypnotizability as measured by the Stanford Hypnotic Clinical Scale (Hilgard & Hilgard, 1975;Kallio & Koivisto, 2013;Költő, Gősi-Greguss, Varga, & Bányai, 2014;Pekala & Maurer, 2013) and pain tolerance scores (Adachi et al, 2014) to be significantly enhanced for Pts exposed to REST immediately afterward and 10-14 days later but not for controls.…”
mentioning
confidence: 91%